1992
DOI: 10.1002/eji.1830221107
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation‐specific expression of a novel G protein‐coupled receptor from Burkitt's lymphoma

Abstract: Deregulation of the proto-oncogene MYC by specific chromosomal translocations has been shown to be essential but not sufficient for the development of Burkitt's lymphoma (BL). To identify other genes which either mark important steps in tumorigenesis or which reflect the cellular differentiation state of BL cells we have compared tumor cells to immortalized lymphoblastoid B cells by subtractive hybridization. We have identified a complementary DNA clone which encodes a novel member of the superfamily of GTP-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 26 publications
3
92
1
Order By: Relevance
“…In this context, the CXCL13-CXCR5 pairing has been shown to be critically involved in the homing of B cells into lymphoid follicles, as well as in the development of organized lymphoid follicles (28,29,40,41). The formation of ectopic lymphoid tissue in chronic inflammatory disease, such as primary SS, is a complex process regulated by an array of cytokines, adhesion molecules, and chemokines (4,13), partly mimicking signals found in normal lymphoid organogenesis (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the CXCL13-CXCR5 pairing has been shown to be critically involved in the homing of B cells into lymphoid follicles, as well as in the development of organized lymphoid follicles (28,29,40,41). The formation of ectopic lymphoid tissue in chronic inflammatory disease, such as primary SS, is a complex process regulated by an array of cytokines, adhesion molecules, and chemokines (4,13), partly mimicking signals found in normal lymphoid organogenesis (42).…”
Section: Discussionmentioning
confidence: 99%
“…Each of the subsets manifested a comparable high frequency of positive cells (mean Ϯ SD 46.4 Ϯ 2.5% in healthy subjects versus 46.1 Ϯ 7.7% in patients with primary SS). Notably, a significantly enhanced frequency of CD27Ϫ naive B cells that expressed CXCR4 transcripts was Both known CXCR5-mRNA splice variants (variant 1 NM_001716 and variant 2 NM_032966; National Center for Biotechnology Information database [28,29]) were analyzed in healthy controls and in patients with primary SS. It was found that individual peripheral B cells expressed either variant 1 (which encodes a protein that is 45 amino acids longer at the N-terminus than isoform 2) or variant 2.…”
Section: Amplification Of Chemokine Receptor Transcripts From Individmentioning
confidence: 99%
“…The observed 91% homology between mouse and human CXCR4 is exceptionally high for members of the chemokine receptor family as only 83% for homology has been reported for human and mouse BLR1/CXCR5 [29,30], 78% homology for CCR1 [31,32], and 63% for CCR3 [32,33]. Together with the fact that SDF-1 shows 99% identity between both species, one is tempted to speculate that both receptor and ligand might serve identical functions in both species.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we report that CXCR5 gene expression is increased ϳ50-fold in both of the DN Treg clones compared with their mutant progeny. CXCR5 was described initially in Burkitt's lymphoma as a G protein-coupled receptor (45) and subsequently found in B cells and a subset of CD4 ϩ T cells (46). More recently, CXCR5 expression has also been shown in DN T cells from MRL-Lpr mice (47).…”
Section: -Fold Higher By Qrt-pcr)mentioning
confidence: 99%